Project Work in CLIL: A Bibliographical Review - Ricardo Casan-Pitarch (Universidad de La Sabana, 2015)
The article "Project work in CLIL: A bibliographical review" has been retracted at the request of the authorities of the Universidad Católica San Antonio de Murcia (Murcia, Spain) as the manuscript was found to contain a substantial amount of content derived without credit or citation from the unpublished work of researchers at that institution. El artículo "El trabajo de proyectos en CLIL: Una revisión bibliográfica" a petición de las autoridades de la Universidad Católica San Antonio de Murcia (Murcia, España) que se encontró el manuscrito para contener una cantidad sustancial de contenido derivado sin crédito o cita de las obras inéditas de investigadores de esa institución. For further information/Para información adicional: http://laclil.unisabana.edu.co/index.php/LACLIL/article/view/6714